Clostridioides difficile infections were predominantly driven by fluoroquinolone-resistant Clostridioides difficile ribotypes 176 and 001 in Slovakia in 2018-2019 - Plankaova, Adriana; Brajerova, Marie; Capek, Vaclav; Balikova Novotna, Gabriela; Kinross, Pete; Skalova, Jana; Soltesova, Anna; Drevinek, Pavel; Krutova, Marcela (International journal of antimicrobial agents, 2023)
AIM: To investigate the epidemiology of Clostridioides difficile infection (CDI) in Slovakian hospitals after the emergence of ribotype 176 (027-like) in 2016. METHODS: Between 2018 and 2019, European Centre for Disease Control and Prevention CDI surveillance protocol v2.3 was applied to 14 hospitals, with additional data collected on recent antimicrobial use and the characterization of C. difficile isolates. RESULTS: The mean hospital incidence of CDI was 4.1 cases per 10,000 patient bed-days. One hundred and five (27.6%) in-hospital deaths were reported among the 381 cases. Antimicrobial treatment within the previous 4 weeks was recorded in 90.5% (333/368) of cases. Ribotype (RT)176 was detected in 50% (n=185/370, 14 hospitals) and RT001 was detected in 34.6% (n=128/370,13/14 hospitals) of cases with RT data. Overall, 86% (n=318/370) of isolates were resistant to moxifloxacin by Thr82Ile in GyrA (99.7%). Multi-locus variable tandem repeat analysis showed clonal relatedness of predominant RTs within and between hospitals. Seven of 14 sequenced RT176 isolates and five of 13 RT001 isolates showed between zero and three allelic differences by whole-genome multi-locus sequence typing. The majority of sequenced isolates (24/27) carried the erm(B) gene and 16/27 also carried the aac(6')-aph(2'') gene with the corresponding antimicrobial susceptibility phenotypes. Nine RT176 strains carried the cfr(E)gene and one RT001 strain carried the cfr(C) gene, but without linezolid resistance. CONCLUSIONS: The newly-predominant RT176 and endemic RT001 are driving the epidemiology of CDI in Slovakia. In addition to fluoroquinolones, the use of macrolide-lincosamide-streptogramin B antibiotics can represent another driving force for the spread of these epidemic lineages. In C. difficile, linezolid resistance should be confirmed phenotypically in strains with detected cfr gene(s).
Keywords: Microbial Sensitivity Tests; Linezolid; Macrolides; Humans; Ribotyping; klostridiové infekce; Multilocus Sequence Typing; Clostridioides; Fluoroquinolones; mikrobiální testy citlivosti; lidé; antibakteriální látky; ribotypizace; Slovakia; linezolid; Slovenská republika; Anti-Bacterial Agents; Clostridium Infections; multilokusová sekvenční typizace; fluorochinolony; makrolidy; Clostridioides difficile